Local Public Finances and Municipal Reform in Finland - André, Christophe (OECD Economics Department Working Papers, 2014)
Finnish municipalities enjoy ample fiscal autonomy and provide or arrange the provision of a large share of public services. In recent years, their spending and debt has been increasing steadily, especially because of population ageing and increases in the cost of health care and social services. Furthermore, small municipalities are often struggling to align service provision with national standards. The government has launched a reform to create more efficient municipalities through voluntary mergers. Both international experience and costs per capita across Finnish municipalities suggest an optimal size for municipalities of over 20 000 inhabitants, at least outside remote areas. As mergers are to be voluntary, the outcome of the reform remains uncertain. If merger plans prove insufficient to achieve efficient public service provision, the government could impose mergers on smaller municipalities, especially around the main urban areas. Responsibilities of smaller municipalities could be scaled back in all functions where economies of scale and scope can be achieved. Policies also need to be flexible enough to allow restructuring of services after mergers. Partnerships between public or private entities to provide services could be developed further in some areas. Finally, the tax structure and fiscal rules should be enhanced to ensure long-term fiscal sustainability. This Working Paper relates to the 2014 OECD Economic Survey of Finland (www.oecd.org/eco/surveys/economicsurvey- finland.htm)